Real-time determination and monitoring of the auroral electrojet boundaries - Johnsen, Magnar Gullikstad (Journal of Space Weather and Space Climate, 2013)
A method for nowcasting of the auroral electrojet location from real-time geomagnetic data in the European sector is presented. Along the auroral ovals strong electrojet currents are flowing. The variation in the geomagnetic field caused by these auroral electrojets is observed on a routine basis at high latitudes using ground-based magnetometers. From latitude profiles of the vertical component of these variations it is possible to identify the boundaries of the electrojets. Using realtime data from ground magnetometer chains is the only existing method for continuous monitoring and nowcasting of the location and strength of the auroral electrojets in a given sector. This is an important aspect of any space weather programme. The method for obtaining the electrojet boundaries is described and assessed in a controlled environment using modelling. Furthermore a provisional, real-time electrojet tracker for the European sector based on data from the Tromsø Geophyiscal Observatory magnetometer chain is presented. The relationship between the electrojet and the diffuse auroral oval is discussed, and it is concluded that although there may exist time-dependent differences in boundary locations, there exists a general coincidence. Furthermore, it is pointed out that knowledge about the latitudinal location of the geomagnetic activity, that is the electrojets, is more critical for space weather sensitive, ground-based technology than the location of the aurora.